The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1074/jbc.m510241200
|View full text |Cite
|
Sign up to set email alerts
|

A pH-dependent Molten Globule Transition Is Required for Activity of the Steroidogenic Acute Regulatory Protein, StAR

Abstract: The steroidogenic acute regulatory protein (StAR) simulates steroid biosynthesis by increasing the flow of cholesterol from the outer mitochondrial membrane (OMM) to the inner membrane. StAR acts exclusively on the OMM, and only StAR's carboxyl-terminal ␣-helix (C-helix) interacts with membranes. Biophysical studies have shown that StAR becomes a molten globule at acidic pH, but a physiologic role for this structural transition has been controversial. Molecular modeling shows that the C-helix, which forms the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 46 publications
5
65
0
1
Order By: Relevance
“…The ⍀ -loops form hydrogen bonds with the C-terminal helix; when these bonds are intact, the C-helix obstructs access of cholesterol to StAR's hydrophobic cholesterol-binding pocket. Molecular Dynamics simulations indicated that the C-helix can "swing open," especially when the surface residues are protonated, as would be expected when StAR interacts with the OMM ( 213 ). It is presumed that the interaction of StAR with the charged phospholipid head groups on the OMM disrupts these such as puromycin or cycloheximide, indicating that a short-lived protein species mediates this process (183)(184)(185).…”
Section: Acute Versus Chronic Regulation Ofmentioning
confidence: 94%
See 3 more Smart Citations
“…The ⍀ -loops form hydrogen bonds with the C-terminal helix; when these bonds are intact, the C-helix obstructs access of cholesterol to StAR's hydrophobic cholesterol-binding pocket. Molecular Dynamics simulations indicated that the C-helix can "swing open," especially when the surface residues are protonated, as would be expected when StAR interacts with the OMM ( 213 ). It is presumed that the interaction of StAR with the charged phospholipid head groups on the OMM disrupts these such as puromycin or cycloheximide, indicating that a short-lived protein species mediates this process (183)(184)(185).…”
Section: Acute Versus Chronic Regulation Ofmentioning
confidence: 94%
“…It was initially noted that the 37 kDa cytoplasmic form possessing the mitochondrial leader sequence had a short half-life of less than 15 min, suggesting it was a "precursor," whereas the 30 kDa intramitochondrial "mature" form of StAR had a half-life of several hours. It was fi rst suggested that importation of StAR into mitochondria formed "contact points" between the OMM and IMM, permitting cholesterol to fl ow down a chemical concentration gradient ( 136,199 ), and others concluded that the 30 kDa "mature" StAR is the biologically active moiety, functioning as a cholesterol shuttle in the intramembranous space lost activity ( 213 ). Thus, the activity of StAR on the OMM requires an acid-induced disruption of hydrogen bonds and a consequent conformational change in StAR to permit it to bind and release cholesterol.…”
Section: Structure and Mechanism Of Star's Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…L'interaction entre l'hélice α4 du domaine START et les têtes protonées des phospholipides de la membrane externe mitochondriale change la conformation de la protéine et ouvre ainsi le couvercle formé par l'hélice α4, donnant accès à la cavité amphiphile du domaine START. En accord avec un rôle crucial de la dynamique de l'hélice α4, des mutants de STARD1 possédant des ponts di-sulfures bloquant la mobilité de l'hélice α4 n'ont plus la capacité de transporter le cholestérol, alors que la réduction de ces ponts di-sulfures restaure le transport [36]. L'import de STARD1 dans la mitochondrie ne serait donc que secondaire à son action et terminerait probablement la stéroïdogenèse.…”
Section: Changement Conformationnel Et Rôle De L'hélice A4unclassified